(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This study investigated the superstitious behavior in college students. Experiment participants were 10 students from different graduate students of both sexes and at the age between 18 and 29 years. The experiment was conducted in one of the cubicles of Goiás PUC LAEC equipped with a computer, mouse and a camcorder. The participants were told that the experiment of course the word “Congratulations” appear on the PC screen. The place was equipped with a paper sheet with a question. The session lasted seven minutes, five occurred in fixed time schedule of 20 seconds and the last two minutes were referring to extinction (TF 20s + Extinction). The video recordings were taken eight categories of the main behavioral phenomena as “manipulation of objects,” for example, and 47 subcategories like “manipulate the keyboard”, “touch paper sheet” and “touch phone.” The study showed that participants had a significant increase in the frequency of responses to manipulate the computer during the two phases of the experiment; most students did not describe the contingency to which they were exposed, then the experiment. Nine participants behaved as if there was a causal relationship between their responses and the presentation of the reinforcer. Thus, the set of relations were not contiguity and contingency and the observed effects can be explained based on the answers that performed at the time the reinforcer was provided.